Study on Mechanism and Suppression Method of Flow-Induced Noise in High-Speed Gear Pump - ZHAN, Peng; QIANG, Yan; JIANG, Zhiyuan; YANG, Runxue; WEI, Liejiang (Archives of Acoustics, 2024)
The flow-induced noise mechanism of a 5000 rpm high-speed gear pump is explored. On the basis of the CFD technology and the Lighthill acoustic analogy theory, a numerical model of the flow-induced noise of a high-speed gear pump is constructed, and the effect of oil suction pressure (0.1–0.2 MPa) on the internal flow field and flow-induced noise characteristics of the high-speed gear pump is investigated. To evaluate the accuracy of the numerical simulation, a noise testing platform for high-speed gear pumps was developed. Adding an oil replenishment groove to the high-speed gear pump suppresses its flow-induced noise. The results indicate that the discrete noise at the fundamental frequency and its harmonic frequency is the primary component of the flow-induced noise of the pump and that the oil-trapped area is the principal source of vibration. The overall sound pressure level of flow-induced noise in the inlet and outlet areas decreases with distance from the oil-trapped area, and the sound pressure level in the outlet area is greater than that in the inlet area. The oil replenishment groove may considerably minimize cavitation noise, enhance the oil absorption capacity, and reduce the outer field’s overall sound pressure level by 4–5 dB.